TUGAS POKOK DAN FUNGSI OPERATOR SEKOLAH DI UPT SPF SMP NEGERI 3 MAKASSAR - Dira Tri Andini; Wahira, Wahira; Sumarlin Mus (Yayasan Nusantara Hasana Berdikari, 2025)
This study aims to describe and analyze the implementation of the main duties and functions of school operators at UPT SPF SMP Negeri 3 Makassar, as well as to identify the supporting and inhibiting factors in their execution. School operators play a vital role in managing digital-based educational data, especially through the Dapodik application. However, they often face excessive workloads, lack of structural support, and limited training opportunities. This research employs a descriptive qualitative approach, utilizing observation, interviews, and documentation as data collection techniques. The findings reveal that school operators hold a strategic position in supporting digital education governance, yet they do not receive structural recognition proportional to their responsibilities. There is a pressing need for policy reformulation and the development of clear standard operating procedures (SOPs) to strengthen their role and improve the professionalism of school operators. These findings contribute significantly to the development of data-driven education policies and the reinforcement of a more inclusive school administrative system.